An Assessment of Resource Suitability and Visitor Perceptions in The Bahowo Mangrove Ecotourism Area - Tommy M. Kontu; Dannie R. S. Oroh; Meidy Wollah; Oktavianus Lintong (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Mangrove ecotourism is a strategic approach to coastal area management that integrates environmental conservation and community empowerment. This study aims to assess the resource suitability level and evaluate visitor perceptions in the Bahowo mangrove ecotourism area, Manado City. Primary data were collected through field surveys using the Tourism Suitability Index (IKW) and perception questionnaires based on a Likert scale. Five ecological parameters were analysed to obtain the IKW score, while six visitor perception aspects were evaluated to assess satisfaction and revisit intention. The results revealed an IKW score of 1.84, classified as "not suitable", primarily due to limited mangrove width (79 m) and low vegetation density (11 ind/100 m²). Although tidal range and biodiversity parameters scored high, their contribution was insufficient to improve the overall suitability classification. Visitor perceptions indicated satisfaction with visual aesthetics, but evaluations of facilities, educational value, and revisit intention were notably low. The ecological unsuitability and poor tourism service quality indicate that Bahowo is currently not ideal for sustainable ecotourism. The study recommends ecosystem improvement through mangrove rehabilitation and enhancement of interpretive infrastructure as prerequisites for developing an adaptive and sustainability-oriented ecotourism area. Keywords: mangrove, ecotourism, suitability, Bahowo Abstrak Ekowisata mangrove merupakan pendekatan strategis dalam pengelolaan kawasan pesisir yang mengintegrasikan konservasi lingkungan dan pemberdayaan masyarakat. Penelitian ini bertujuan untuk menilai tingkat kesesuaian sumber daya dan mengevaluasi persepsi pengunjung di kawasan ekowisata mangrove Bahowo, Kota Manado. Data primer dikumpulkan melalui survei lapangan dengan pendekatan Indeks Kesesuaian Wisata (IKW) dan kuesioner persepsi berbasis skala Likert. Lima parameter ekosistem dianalisis untuk memperoleh nilai IKW, sedangkan enam aspek persepsi pengunjung dievaluasi guna mengetahui kepuasan dan niat kunjungan ulang. Hasil menunjukkan nilai IKW sebesar 1,84 yang termasuk kategori “tidak sesuai”, disebabkan oleh ketebalan mangrove (79 m) dan kerapatan vegetasi (11 ind/100 m²) yang rendah. Meskipun pasang surut dan keanekaragaman biota menunjukkan skor tinggi, kontribusinya tidak cukup untuk menaikkan kelas kesesuaian. Persepsi pengunjung mengindikasikan kepuasan terhadap keindahan visual, namun penilaian terhadap fasilitas, nilai edukatif, dan intensi kunjungan ulang tergolong rendah. Ketidaksesuaian ekologis dan rendahnya layanan wisata menunjukkan bahwa kawasan Bahowo saat ini belum ideal untuk ekowisata berkelanjutan. Penelitian ini merekomendasikan perbaikan ekosistem melalui rehabilitasi mangrove dan penguatan infrastruktur interpretatif sebagai prasyarat pengembangan kawasan ekowisata yang adaptif dan berorientasi pada keberlanjutan. Kata kunci: mangrove, ekowisata, kesesuaian, Bahowo